(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Abstract: Development experience in western countries suggests that output can be increased at a much faster rate as compared to increase in physical units such as labour and physical capital. It has possible due to improvement in the quality of human beings in the production system and that too has also been resulted from improvement in education and skills, availability health services, improvement in training facilities etc. Development of any country in the world completely depends on the human resource development. Thus developing human resources means improving the quality of human beings which in turn helps adequately in the process of attaining growth and development of the country’s economy. Education is an important factor determining the nature of human resources of a country. The quality of education available in a country determines the quality of human capital. Education simply implies a process of teaching, learning and training set up especially in schools, colleges, universities, technical institutes etc. for improving the level of knowledge. Education is considered as the most important tool for bringing faster economic and social change in any country. Thus education paves the way for developing necessary skills for improving working abilities of people commonly. Thus education is responsible for reduce income inequalities, economic growth, family planning and rural development etc. This paper made an attempt to identify the Government expenditure towards social services in connection with education, health and other sectors, and also to know the growth of education sector in India. The data has been collected from various secondary sources.